A REPRESENTATION OF FEMINISM IN SCIENCE FICTION FILM (SEMIOTIC ANALYSIS RELATED TO FILM LEVEL 16) - Sormin, Ilham habibi; Muhammad Dalimunthe; Syahrul Abidin (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2022)
The development of the film world is very diverse and produces films with various styles. Broadly speaking, films can be grouped by story, making orientation, and by genre. This study aims to determine the representation of feminism contained in the science fiction film entitled Level 16. This study uses a qualitative method with the semiotic analysis technique of Ferdinand De Saussure's model which examines the signs in life. Through this method, several scenes are selected in the level 16 film, then these scenes are revealed into denotative and connotative meanings and then interpreted in signifier and signified. In this study, the researcher found ten scenes that presented feminism in level 16 films.